2010
DOI: 10.1074/jbc.m110.133280
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymorphisms of Nuclear Receptor SHP Associated with Functional and Structural Changes

Abstract: We identified three heterozygous nonsynonymous single nucleotide polymorphisms in the small heterodimer partner (SHP, NROB2) gene in normal subjects and CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy)-like patients, including two novel missense mutations (p.R38H, p.K170N) and one of the previously reported polymorphism (p.G171A). Four novel heterozygous mutations were also identified in the intron ( Intron 1265T3 A), 3-untranslated region ( 3-UTR 101C3 G, 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 41 publications
2
62
0
Order By: Relevance
“…After 24 hours, wild‐type AURKA 3′‐UTR and LIN28B 3′‐UTR or their seed mutant luciferase reporter vectors with miR‐26a‐5p mimic or miR‐29a‐3p mimic were transfected into the cells using RNAiMAX transfection reagent. The dual‐luciferase reporter assay system (Promega, Madison, WI) was applied 48 hours after transfection to determine changes in relative luciferase units as described 24. All assays were performed in triplicate, and all values were normalized for transfection efficiency against Renilla luciferase activities.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hours, wild‐type AURKA 3′‐UTR and LIN28B 3′‐UTR or their seed mutant luciferase reporter vectors with miR‐26a‐5p mimic or miR‐29a‐3p mimic were transfected into the cells using RNAiMAX transfection reagent. The dual‐luciferase reporter assay system (Promega, Madison, WI) was applied 48 hours after transfection to determine changes in relative luciferase units as described 24. All assays were performed in triplicate, and all values were normalized for transfection efficiency against Renilla luciferase activities.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in the SHP-EID1 interface disrupt EID1 binding to SHP. Together, these results provide crucial mechanistic insights into SHP-mediated cofactor recruitment and repression (24,28,30).…”
Section: Arillmastlknipgtllvdlffrpimgdvditelledmlllr-aelnsalfllrfinsdmentioning
confidence: 80%
“…A number of proteins have been isolated as SHP corepressors, including histone deacetylases (SIRT1, HDAC1, and HDAC3) (25,28) and EID1, which inhibits p300/CBP HAT activity (24,26,27). However, the mechanism whereby these corepressors interact with SHP has been poorly understood.…”
Section: Arillmastlknipgtllvdlffrpimgdvditelledmlllr-aelnsalfllrfinsdmentioning
confidence: 99%
See 1 more Smart Citation
“…This was accompanied by increased recruitment of HNF4a to the promoter of CYP2D6 (Koh et al, 2014). The enhanced HNF4a activity during pregnancy was attributed in part to the decreased expression of small heterodimer partner (SHP) (Koh et al, 2014), a corepressor that inhibits HNF4a activity via physical interaction (Zhou et al, 2010). Interestingly, our results showed that other target genes of HNF4a (such as Hes6 and ApoC2) did not exhibit similar increases in expression to CYP2D6 during pregnancy in tg-CYP2D6 mice (Koh et al, 2014).…”
Section: Introductionmentioning
confidence: 68%